Enhancing digital literacy skills among teachers for effective integration of computer science and design education: a case study at Astana International School, Kazakhstan - Temirkhanova, Meruyert; Abildinova, Gulmira; Karaca, Celal (Frontiers in Education, 2024)
This study explores the development and impact of digital literacy skills among teachers at Astana International School, Kazakhstan, and examines how these skills influence the teaching of Computer Science and Design to middle school students. Employing a mixed-methods approach, the research combined quantitative assessments of students' proficiency with qualitative evaluations of teacher and student experiences, involving 71 teachers and 382 students from grades 7 to 10. The findings indicate that students taught by digitally literate teachers demonstrated significant improvements in designing and utilizing virtual reality tools, mobile applications, and other digital resources, with teachers facilitating more interactive and engaging learning environments that enhanced students' technical skills and creative capacities. This research contributes new insights into the dynamics of digital literacy in education, emphasizing the critical role of teacher training in digital tools for enhancing educational practices and uniquely demonstrating how systematic application of digital literacy can transform educational outcomes, supporting the integration of technology in teaching, aligned with the needs and competencies of Generation Z students.